The Chemokine CCL5 Inhibits the Replication of Influenza A Virus Through SAMHD1 Modulation - Silva, Thauane; Temerozo, Jairo R.; do Vale, Gabriele; Ferreira, André C.; Soares, Vinícius Cardoso; Dias, Suelen Silva Gomes; Sardella, Gabriela; Bou-Habib, Dumith Chequer; Siqueira, Marilda; Souza, Thiago Moreno L.; Miranda, Milene (Frontiers in Cellular and Infection Microbiology, 2021)
Influenza A virus (IAV) is the main etiological agent of acute respiratory tract infections. During IAV infection, interferon triggers the overexpression of restriction factors (RFs), the intracellular antiviral branch of the innate immune system. Conversely, severe influenza is associated with an unbalanced pro-inflammatory cytokine release. It is unclear whether other cytokines and chemokines released during IAV infection modulate RFs to control virus replication. Among the molecules enhanced in the infected respiratory tract, ligands of the CCR5 receptor play a key role, as they stimulate the migration of inflammatory cells to the alveoli. We investigated here whether ligands of the CCR5 receptor could enhance RFs to levels able to inhibit IAV replication. For this purpose, the human alveolar basal epithelial cell line (A549) was treated with endogenous (CCL3, CCL4 and CCL5) or exogenous (HIV-1 gp120) ligands prior to IAV infection. The three CC-chemokines tested reduced infectious titers between 30% to 45% upon 24 hours of infection. Eploying RT-PCR, a panel of RF mRNA levels from cells treated with CCR5 agonists was evaluated, which showed that the SAMHD1 expression was up-regulated four times over control upon exposure to CCL3, CCL4 and CCL5. We also found that IAV inhibition by CCL5 was dependent on PKC and that SAMHD1 protein levels were also increased after treatment with CCL5. In functional assays, we observed that the knockdown of SAMHD1 resulted in enhanced IAV replication in A549 cells and abolished both CCL5-mediated inhibition of IAV replication and CCL5-mediated cell death inhibition. Our data show that stimuli unrelated to interferon may trigger the upregulation of SAMHD1 and that this RF may directly interfere with IAV replication in alveolar epithelial cells.